Organocatalytic Green Approach Towards the Fabrication of Fused Benzo N, N‐containing Heterocycles Facilitated by Ultrasonic Irradiation. (22nd August 2019) - Nongrum, Ridaphun; Kharmawlong, George Kupar; Rani, Jims World Star; Rahman, Noimur; Dutta, Arup; Nongkhlaw, Rishanlang
Abstract : The development of a metal‐free protocol for transformations in organic synthesis offers a significant potential environmental benefit. This article reports the exploration of meglumine, a nontoxic and biodegradable amino sugar, as an organocatalyst for the synthesis of biologically active 1 H ‐dibenzo[ b, e ][1, 4]diazepin‐1‐ones, highly regioselective benzimidazole derivatives and derivatives of quinoxalines. Operational simplicity, mild reaction conditions, shorter reaction times, and use of green solvents are the highlights of this protocol. The advantage of ultrasonic irradiation has been significantly explored for the synthesis of the aforesaid compounds. Furthermore, the multifaceted use of o ‐phenylenediamine has also been accentuated in the study. Abstract :